Results for sixth order positively homogeneous equations - Garbuza, Tatjana (Mathematical Modelling and Analysis, 2009)
We consider positively homogeneous the sixth order differential equations of the type x (6) = h(t, x), where hpossesses the property that h(t, cx) = ch(t, x) for c ≥ 0. This class includes the linear equations x (6) = p(t)x and piece‐wise linear ones x (6) = k 2 x+ - k 1 x− . We consider conjugate points and angles associated with extremal solutions and prove some comparison results. First published online: 14 Oct 2010